2016
DOI: 10.1093/ijnp/pyw047
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Prevents Dopaminergic Neuron Death in MPTP/P-Induced Mouse Model of Parkinson’s Disease via Autophagy and Mitochondrial ROS Clearance

Abstract: Background:Our previous study demonstrated that metabolic inflammation exacerbates dopaminergic neuronal degeneration in type 2 diabetes mice. Metformin, a typical oral hypoglycemic agent for diabetes, has been regarded as an activator of AMP-activated protein kinase and a regulator of systemic energy metabolism. Although metformin plays potential protective effects in many disorders, it is unclear whether metformin has a therapeutic role in dopaminergic neuron degeneration in Parkinson’s disease.Methods:In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(144 citation statements)
references
References 43 publications
7
137
0
Order By: Relevance
“…Another recent study has also shown that metformin, an MTORC1 inhibitor currently used to treat type 2 diabetes, may activate autophagy flux in the SN of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine/probenecid (MPTPp) mouse model of PD. Metformin attenuates inflammasome activation and pro-inflammatory cytokine TNF-α and IL-6 levels while increasing anti-inflammatory IL-10 levels [161], suggesting that autophagy may control the SN inflammatory response in an in vivo model of PD. However, this report did not provide evidence of the specific role of microglia on MPTPp elicited PD-like inflammatory response.…”
Section: Autophagy and Microglial Inflammation During Aging And Nementioning
confidence: 99%
“…Another recent study has also shown that metformin, an MTORC1 inhibitor currently used to treat type 2 diabetes, may activate autophagy flux in the SN of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine/probenecid (MPTPp) mouse model of PD. Metformin attenuates inflammasome activation and pro-inflammatory cytokine TNF-α and IL-6 levels while increasing anti-inflammatory IL-10 levels [161], suggesting that autophagy may control the SN inflammatory response in an in vivo model of PD. However, this report did not provide evidence of the specific role of microglia on MPTPp elicited PD-like inflammatory response.…”
Section: Autophagy and Microglial Inflammation During Aging And Nementioning
confidence: 99%
“…In SH-SY5Y cells, metformin effectively suppressed cell proliferation, invasion potential, and sphere-forming ability [21,22]. On the contrary, metformin attenuated the cytotoxicity induced by 1-methyl-4-phenylpyridinium (MPP + ) [23] or α-synuclein [24] in SH-SY5Y cells. Interestingly, it was reported that lowering the glucose level potentiated metformin-induced cytotoxicity in breast cancer cells [25].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these effects was prevented by the AMPK inhibitor compound C and by the macroautophagy inhibitor 3-Methyladenine (3-MA). These findings suggest that AMPK activation via metformin is neuroprotective through multiple mechanisms, including decreased neuroinflammation, clearance of αSyn, and increased mitochondrial quality control [170]. Similar results were observed in mice treated with MPTP for 1 week followed by 1 week of metformin treatment [171].…”
Section: Ampk Activation As a Treatment Strategy For Pdmentioning
confidence: 52%
“…Metformin is the most widely prescribed medication for type-2 diabetes (T2D) and has well-established effects in the liver but is also taken up in the brain [169]. Treatment of mice with metformin for 5 weeks significantly ameliorated MPTP-induced degeneration of SNc DA neurons, partially restored striatal DA content, and fully restored normal motor behavior on the rotarod test [170]. Metformin also increased macroautophagy, reduced αSyn, decreased reactive microglia, and attenuated expression of proinflammatory cytokines.…”
Section: Ampk Activation As a Treatment Strategy For Pdmentioning
confidence: 99%